Deterrence Effect in The Making: The Strategic Role of Indonesia’s Maritime Law in ASEAN - Rizki Marman Saputra; Gumilar Rusliwa Somantri; Athor Subroto (Universitas Negeri Semarang, 2025)
Indonesia’s maritime influence constitutes a central pillar of security stability in Southeast Asia, particularly in the strategically significant waters of the Malacca Strait. This article examines Indonesia’s contribution to regional deterrence through three core research questions: (1) How does the Indonesian Navy’s capability shape its deterrence posture in the Malacca Strait? (2) What constraints hinder Indonesia from establishing a credible deterrence effect within the ASEAN security framework? and (3) How can Indonesia’s strategic location and maritime diplomacy be optimized to enhance regional stability?. Using a qualitative methodology that integrates expert interviews and document analysis, the study finds that Indonesia’s deterrence posture remains constrained by limited defense modernization, inconsistent strategic communication, and uneven policy execution. Furthermore, structural issues such as budgetary constraints and the consensus-based nature of ASEAN diplomacy have reduced Indonesia’s ability to respond effectively to maritime provocations. Despite these challenges, Indonesia continues to act as a stabilizing anchor within ASEAN’s maritime security architecture. The findings highlight that advancing naval capability, institutionalizing maritime diplomacy based on international law, and integrating legal and strategic frameworks are crucial to building a layered deterrence effect. Ultimately, Indonesia’s Global Maritime Fulcrum (GMF) vision can evolve into a coherent maritime defense doctrine—transforming maritime law from a regulatory instrument into a strategic tool that reinforces both national sovereignty and ASEAN’s collective resilience in an increasingly contested Indo-Pacific order.